Gut microbial metabolites and the brain–gut axis in Alzheimer’s disease: A review - Xinchen Ji; Jian Wang; Tianye Lan; Dexi Zhao; Peng Xu (Biomolecules & Biomedicine)
Alzheimer’s disease (AD) is increasingly recognised as a disorder that extends beyond the brain, with accumulating evidence implicating gut microbiota–derived metabolites in its onset and progression. This narrative review synthesises 92 peer-reviewed animal, human and meta-analytic studies published between 2010 and 2025 that investigated short-chain fatty acids (SCFAs), tryptophan-derived indoles and kynurenines, trimethylamine N-oxide (TMAO) and secondary bile acids in the context of AD. Collectively, the literature shows that SCFAs support blood–brain-barrier integrity, dampen microglial reactivity and enhance synaptic plasticity, yet can paradoxically amplify β-amyloid (Aβ) deposition under germ-free or supraphysiological conditions, highlighting the importance of host status and dosing. Beneficial indole metabolites such as indole-3-propionic acid counter oxidative stress, strengthen intestinal and cerebral barriers and suppress pro-inflammatory cascades, whereas a shift toward neurotoxic kynurenines correlates with cognitive decline. TMAO emerges as a consistently deleterious metabolite that aggravates endothelial dysfunction, neuroinflammation and Aβ aggregation; dietary precursor restriction and microbial enzyme inhibitors are therefore being explored as mitigation strategies. Secondary bile acids and polyphenol derivatives further modulate mitochondrial bioenergetics and NF-κB signalling, broadening the therapeutic landscape. Multi-omics profiling reveals that AD patients typically exhibit reduced SCFAs and indoles but elevated TMAO, changes that scale with Mini-Mental State Examination scores, brain atrophy and cerebrospinal Aβ₄₂ levels. Early probiotic and faecal-microbiota-transplant trials have begun to normalise these metabolite profiles and yield modest cognitive benefits, underscoring translational potential. Altogether, gut-derived metabolites are not passive by-products but active modulators of neural, immune and metabolic circuits along the microbiota–gut–brain axis; their targeted manipulation and standardised metabolomic assessment could enable earlier diagnosis and precision microbiome-based interventions for AD, a promise that now warrants validation in large, longitudinal and mechanistically informed clinical studies.